Elimination of sulfates from wastewaters by natural aluminosilicate modified with uric acid; Resource-Efficient Technologies; Vol. 1, Iss. 2 - De Los Santos J.; Cornejo-Bravo J. M.; Castillo E.; Bogdanchikova N.; Farias S. M.; Mota-Morales J. D.; Reynoso E. S.; Pestryakov A. N. Aleksey Nikolaevich; Rodriguez Ventura J. G. (2015, 2015)
Title screen